1989
DOI: 10.1111/j.1365-3083.1989.tb01127.x
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Interleukin 6‐Like B‐Cell Differentiation Factor Production in Human Adherent Synovial Cells by Recombinant Interleukin 1

Abstract: Abnormal production of immunoglobulin in the joint space is frequently observed in patients with rheumatoid arthritis (RA). We have previously demonstrated that adherent synovial cells (ASC) from patients with RA are involved in B-cell differentiation by their spontaneous production of B-cell differentiation factor (BCDF). The regulation of the production of this factor, however, has not yet been described. We investigated the effects of recombinant interleukin 1 alpha and beta (rIL-1 alpha and rIL-1 beta) on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
1994
1994

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Recent studies from several laboratories have demonstrated that the steady state metabolism of chondrocytes is affected by factors such as insulin-like growth factors IGF-I and IGF-II [5,6], transforming growth factor [7,8], and interleukin-1 (IL-1) [9][10][11][12][13][14][15]. Increased concentrations of interleukin-6 have been found in the synovial fluid of patients with osteoarthritis, rheumatoid arthritis, and crystal-related joint diseases [16][17][18]. Since IL-1 appears to be the major stimulator of interleukin-6 (IL-6) synthesis in many different cell types (reviewed in [19]), we asked the question, whether chondrocytes can also be stimulated to synthesize IL-6.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies from several laboratories have demonstrated that the steady state metabolism of chondrocytes is affected by factors such as insulin-like growth factors IGF-I and IGF-II [5,6], transforming growth factor [7,8], and interleukin-1 (IL-1) [9][10][11][12][13][14][15]. Increased concentrations of interleukin-6 have been found in the synovial fluid of patients with osteoarthritis, rheumatoid arthritis, and crystal-related joint diseases [16][17][18]. Since IL-1 appears to be the major stimulator of interleukin-6 (IL-6) synthesis in many different cell types (reviewed in [19]), we asked the question, whether chondrocytes can also be stimulated to synthesize IL-6.…”
Section: Introductionmentioning
confidence: 99%